4-inch transparent plates based on thin-film AlN actuators for haptic applications. (December 2016) - Casset, F.; Danel, JS.; Renaux, P.; Chappaz, C.; Bernard, F.; Sednaoui, T.; Basrour, S.; Desloges, B.; Fanget, S.
Abstract: Numerous applications require tactile interfaces today. In particular, many customers' applications such as automotive, Smartphone, tablet PC or touch pad can be concerned by high performances, low voltage haptic interfaces which allow the user to interact with its environment by the sense of touch. This technology is already used but with limitations such as high power consumption and limited feedback effect because today a simple vibration is commonly obtained. We chose to work on the squeeze-film effect. It consists in changing the friction between the finger and a plate resonator. It provides high granularity level of haptic sensation. This paper deals with the design, realization and characterization of high performances actuators in order to promote the squeeze-film effect on a 4-inch transparent plate (diagonal of the plate). Using Finite Element Method (FEM) models, we select the best design, able to generate the highest plate displacement amplitude as possible. We built demonstrators using a generic technology based on thin-film Aluminum Nitride (AlN) actuators on glass substrate. Electromechanical characterizations prove that it is possible to obtain the focused substrate vibration amplitude using only 35 V in amplitude. The integration of the thin-film actuator plate in a haptic demonstrator is now ongoing.